42 A review of mortality in patients who undergo ICD insertion in a single implantation centre. (30th September 2020) - Wheen, P; Sharif, Z; O'Carroll-Lolait, C; Moore, D
Abstract : Aims: To review the ICD implantation rate in our institution, as well as to assess overall survival following ICD implantation, and to review the rate of early mortality (<1 year) following ICD insertion. Methods: Using the HeartRhythmIreland.com database, where all new ICD implants have been registered since 2005, we obtained information on demographics, implantation date, last registered visit, and notification of death. Date of death was confirmed with our own institution's electronic patient manager. Survival probability was calculated using the Kaplan-Meier method, using the most recent attended ICD check, or the date of death. Survival was defined as freedom from death at most recent check. (Figure 1 ). Results: 415 ICDs were implanted in our institution between 2005 and 2018. The mean (mean (± SD)) age was 58.9 years (± 14.00) and 333 (80.2%) of the patients were male. These include 80 CRT-Ds, 121 Dual chamber ICDs, 206 Single Chamber ICDs, and 7 Subcutaneous-ICDs (SICD). (Figure 2 ). In the case of upgrades, only the most recent device was included. 3 ICDs were explanted without replacement, 2 due to infection, and 1 due to heart transplant. 95 patients (22.9%) with local follow up died (in whom a date of death is available in 87 patients). 4 (1.0%) patients were lost to follow up. 6 (1.4%) patients emigrated, and 21 (5.1%) patients moved hospital within the state. Among the patients not known to have died or moved centre, the mean duration since the most recent ICD check was 4.8 months. Of the patients who died, the mean time between device insertion and death was 51.6 months ± 30.2, and 6 (1.4%) patients died within a year of ICD insertion. Survival probability at 1, 3 and 5 years was 97.9%, 88.7% and 79.6% respectively. Discussion: This study shows the increasing burden, and complexity, of devices being implanted within our centre. Despite our study not differentiating between primary and secondary prevention, our study shows reassuring survival probability at 5 years when compared with SCD HEF (71.1%) and at 3 years when compared with MADIT (78%).